Nurses' Perception of Family-Centered Care in Neonatal Intensive Care Units - Heidari, Haydeh; Mardani-Hamooleh, Marjan (Journal of Pediatric Intensive Care, 2020)
Family-centered care (FCC) is one of the important elements of care in neonatal intensive care units (NICUs). The aim of this study was to understand the nurses' perception of FCC in NICUs. This qualitative study was performed using conventional content analysis. Participants in this study included 18 nurses who were selected by a purposeful method. Semistructured, in-depth and face-to-face interviews were conducted with the participants. All interviews were written down, reviewed, and analyzed. Two categories were identified after the data analysis: (1) prerequisite for providing FCC and (2) parents' participation. Prerequisite for providing FCC consisted of two subcategories namely suitable facilities and adequate personnel. Parents' participation included subcategories of parents: neonate's attachment and parents' training. Nurses' perception of FCC in NICUs can facilitate an appropriate condition for the participation of family members in the care of neonates.
Keywords: neonatal intensive care unit; family-centered care; nurses' perception